2015
DOI: 10.1007/s00213-015-4081-0
|View full text |Cite|
|
Sign up to set email alerts
|

The continuous performance test (rCPT) for mice: a novel operant touchscreen test of attentional function

Abstract: RationaleContinuous performance tests (CPTs) are widely used to assess attentional processes in a variety of disorders including Alzheimer’s disease and schizophrenia. Common human CPTs require discrimination of sequentially presented, visually patterned ‘target’ and ‘non-target’ stimuli at a single location.ObjectivesThe aims of this study were to evaluate the performance of three popular mouse strains on a novel rodent touchscreen test (rCPT) designed to be analogous to common human CPT variants and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 74 publications
6
80
0
Order By: Relevance
“…Given that mice can learn this version of SAT, it is likely that they could also learn a touchscreen version. In fact, touchscreen versions of 5-CSRTT task and rCPT have been developed for mice, indicating that mice can acquire touchscreen attention tasks (Kim et al, 2015; Romberg et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that mice can learn this version of SAT, it is likely that they could also learn a touchscreen version. In fact, touchscreen versions of 5-CSRTT task and rCPT have been developed for mice, indicating that mice can acquire touchscreen attention tasks (Kim et al, 2015; Romberg et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The touchscreen can be easily programmed for different tasks, and cues and levers are not permanently configured for one specific procedure. Other attention tasks, such as the 5-choice serial reaction time task (5-CSRTT) and the continuous performance task (rCPT), which measure sustained and selective attention (Armstrong, 1997; Kremen et al, 1992; Robbins, 2002), have been modified for use in these chambers (Bartko et al, 2011; Kim et al, 2015). In this methods paper, we explain how to adapt SAT to touchscreen operant chambers for rats.…”
Section: Introductionmentioning
confidence: 99%
“…odour); this assesses rule learning and discrimination [24]. Rodent touchscreen technology, in which rodents need to respond to 'target' visual pattern stimuli and to withhold responses to 'non-target' stimuli, permits assessment of perceptual discrimination, object-place associative learning, attention, impulsivity, compulsivity, extinction and other domains [26,27].…”
Section: Schizophrenia-relevant Behaviour In Rodentsmentioning
confidence: 99%
“…The 5CSRTT, 5C-CPT and SAT were recommended by CNTRICS for further development . To date, results from the touchscreen CPT have only been reported in a single study in mice (Kim et al, 2015) and although further studies in rats were indicated in a review , they have not yet been published. This task may be a promising new avenue for research in the future, however the lack of data limit comparisons being made with the other more widely used tasks at this point in time.…”
Section: Rodent Tasks 151 Current Tasksmentioning
confidence: 99%
“…The closest equivalent tasks to human CPT testing in rodents are the 5-choice serial reaction time task (5CSRTT), the 5-choice continuous performance task (5C-CPT), the sustained attention task (SAT) and more recently the touchscreen CPT task (McGaughy and Sarter, 1995a;Bari et al, 2008;Young et al, 2009b;Kim et al, 2015). The 5CSRTT, 5C-CPT and SAT were recommended by CNTRICS for further development .…”
Section: Rodent Tasks 151 Current Tasksmentioning
confidence: 99%